A Causal Model of Relationship between Organizational Climate Influencing Happiness at Work and Organization Engagement - Ekkasit Sanamthong; Suebpong Prabyai (Ital Publication, 2023)
This research aimed to study the level of organizational climate, happiness at work, and organization engagement. It included research into the relationship between organizational climate and employee happiness and engagement, as well as the direct and indirect effects of organizational climate on employee happiness and engagement. A sample of 400 employees was used. The findings revealed the following: 1) Organizational Climate (OC) directly influencing Happiness at Work (HW) had an influence coefficient of 0.92 with a statistical significance level of 0.05. 2) Organizational Climate (OC) directly influencing Organization Engagement (OE) had the influence coefficient of 0.32 with the statistical significance at the level of 0.05 and indirectly influencing Organization Engagement (OE) through Happiness at Work (HW) had the influence coefficient of 0.59 with the statistical significance at the level of 0.05. 3) Happiness at Work (HW) directly influencing Organization Engagement (OE) had an influence coefficient of 0.64 with a statistical significance level of 0.05. 4) Organizational Climate (OC) could forecast 85 percent of Happiness at Work (HW). 5) Organizational Climate (OC) and Happiness at Work (HW) could jointly forecast 89 percent of Organization Engagement (OE). Doi: 10.28991/ESJ-2023-07-02-018 Full Text: PDF